Penerapan Ragam Hias Neq Limbongan dan Pa’ Kapu Baka Toraja pada Busana Pesta Wanita - Ayu, Wa Ode Nika; Russanti, Irma (BAJU: Journal of Fashion and Textile Design Unesa, 2022)
Ragamhias Neq Limbongandan Pa’kapu Baka yang berasal dari Sulawesi menjadi sumber inspirasi dalam pembuatan karya busana. Tujuan dari penciptaan karya yaitu untuk mengetahui proses penerapan ragam hias Neq Limbongan dan Pa’kapuBakaToraja dan hasil jadinya pada busana pesta wanita. Metode yang digunakan adalah Double Diamond Model, yang terdiri dari 4 tahapan yaituDiscover, Define,Develop, Deliver. Proses penerapan ragan hias Neq Limbongandan Pa’kapu Baka tersebut menggunakan teknik lekapan bordir dengan payet dengan tusuk jelujur. Penerapan ragam hias Neq Limbongandan Pa’kapu Baka pada busana pesta wanitaterletak pada bagian badan depandan badan belakang berbentuk V. Hasil jadi penerapan ragam hias Neq Limbongandan Pa’kapu BakaToraja pada busana pesta wanita dengan siluet mermaid secara keseluruhan menerapkan prinsip desain antara lain harmoni, keseimbangan dan pusat perhatian. The ornamental variety of Neq Limbongan and Pa’kapu Baka originating from Sulawesi is a source of inspiration in making fashion works. The purpose of creating the work is to find out the process of applying the ornamental variety of Neq Limbongan and Pa’kapu Baka Toraja and the finished product to women’s party dress. The method used is the Double Diamond Model, which consists of 4 stages, namely Discover, Define, Develop, Deliver. The process of applying Neq Limbongan and Pa’kapu Baka ornamental ragan usesembroidery technique with sequins with skewers. The application of Neq Limbongan and Pa’kapu Baka ornaments in women’s party clothing lies in the V-shaped face and back body. The finished result of the application of Neq Limbongan and Pa’kapu Baka Toraja ornamental varieties in women’s party dressapplies design principles including harmony, balance,and the center of attention. The application of Neq Limbongan and Pa’kapu Baka ornaments in women’s party clothing lies in the V-shaped front and back body. The finished result of applying the ornamental variety of Neq Limbongan and Pa’kapu Baka Toraja to women’s party clothing with mermaid silhouettes applies design principles including harmony, balance, and the center of interest.